Is Amoxicillin Effective in Treatment of Acute Otitis Media in Routine Outpatient Practice? - Sane, Sudhir V; Balip, Jayashree R; Vernekar, Shwetha (Pediatric Infectious Disease (New Delhi), 2022)
Aim and objective: To evaluate the effectiveness of low-dose amoxicillin in otitis media. Materials and methods: All children presenting to our outpatient clinic with signs and symptoms suggestive of otitis media and need of antibiotics according to AAP criteria were enrolled. Intervention: A 10-day course of oral amoxicillin at 40 mg/kg/day in three divided doses. Main outcome: Symptomatic relief after 48 hours and normal tympanic membrane at the end of therapy. Results: There were 201 cases. One hundred and sixty-one out of these completed a 10-day course of amoxicillin. One hundred and forty-six (90.68%. 95% CI 86.17–95.18%) responded to amoxicillin. On follow-up of these 67.44% had normal tympanic membrane whereas 33.56% had persistent middle ear fluid. Conclusion: Amoxicillin remains the first-line therapy in the treatment of acute otitis media (AOM) in children.